Analyzing the Performance Indicators of Microfinance Institutions in Madhya Pradesh: Examining the Impact of Microfinance Institutions on Poverty Reduction in Madhya Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is one of the developing countries on the planet where poverty is figured as serious issue. Since freedom, the nation put weight on giving financial services as help to poor individuals. For over 30 years microfinance has been depicted as a key strategy and essential financial initiative for poverty decrease and financial advancement. Microfinance is fundamentally a Nobel substitute for financial services offered to lower income and defenseless individuals in different countries and amazing instrument for poverty decrease. Microfinance is the arrangement for a wide scope of financial services to the poor and low income families and their microenterprises. The services incorporate stores, loans, installment services, cash exchanges, and insurance items. Microfinance plot gives a wide scope of financial services to individuals who have close to nothing or nothing in the method for conventional insurance. It encourages them to develop resources, endure emergencies and to build up private venture to leave poverty. But expanding little loans (micro-credit), microfinance program gives different other financial and non-financial services, for example, savings, insurance, direction, skill advancement training, limit building and inspiration to begin income creating exercises to upgrade the profitability of credit. In this work we will study and analyze the basic performance indicators of the selected MFIs in Madhya Pradesh.